ASSESING THE EFFECTIVENESS OF RELIGIOUS LEADERS IN MAINTAINING PEACE AND HARMONY WITH RESPECT TO NEUTRALITY, SPHERE OF INFLUENCE, COMMITMENT AND INTER-ETHNIC RELATIONS THE CASE OF SILTIE SOCIETY - Ezedin Fedlu Nuri (International Journal of Innovations in Engineering Research and Technology, 2023)
Religious leaders as actors of peacemaking could act as both peacemakers (connectors) and conflict instigators (dividers). To this end the study aimed at examining the effectiveness of religious leaders in maintaining and harmony in the case of Siltie society with respect to Neutrality, sphere of influence, commitment and inter-ethnic relations. The study was based on a questionnaire data collected from 355 randomly selected city residents the Siltie society living in Addis Ababa. The quantitative data collected from the questionnaire were triangulated with qualitative data obtained from FGD with members of the society and in-depth interview with interviewees. Descriptive analysis was used to analyze the data. The results showed diverse view of respondents for different measures towards peacemaking performances of religious leaders. Meanwhile their role is generally termed constructive, but not well enough and compiled with limitations. Especially their positive performance is blemished by few newly dvloping biasness of religious leaders towards their ethnicity and this in turn affected the perception of the society in the context of enter-ethnic interactions.